A double-blind randomised controlled trial testing the effect of a barley product containing varying amounts and types of fibre on the postprandial glucose response of healthy volunteers. Issue 9 (8th April 2015) - Ames, Nancy; Blewett, Heather; Storsley, Joanne; Thandapilly, Sijo J.; Zahradka, Peter; Taylor, Carla
Abstract : The aim of the present study was to determine if the consumption of barley tortillas varying in fibre and/or starch composition affected postprandial glucose, insulin, glucagon-like peptide-1 (GLP-1) or peptide YY concentrations. A double-blind, randomised, controlled trial was performed with twelve healthy adults. They each consumed one of five barley tortillas or a glucose drink on six individual visits separated by at least 1 week. Tortillas were made from 100 % barley flour blends using five different milling fractions to achieve the desired compositions. All treatments provided 50 g of available carbohydrate and were designed to make the following comparisons: (1) low-starch amylose (0 %) v . high-starch amylose (42 %) with similar β-glucan and insoluble fibre content; (2) low β-glucan (4·5 g) v . medium β-glucan (7·8 g) v . high β-glucan (11·6 g) with similar starch amylose and insoluble fibre content; and (3) low insoluble fibre (7·4 g) v . high insoluble fibre (19·6 g) with similar starch amylose and β-glucan content. Blood was collected at fasting and at multiple intervals until 180 min after the first bite/sip of the test product. Amylose and insoluble fibre content did not alter postprandial glucose and insulin, but high-β-glucan tortillas elicited a lower glucose and insulin response as compared to the low-β-glucan tortillas. The tortillas with high insoluble fibre had a higher AUC for GLP-1 as compared to the tortillas with low insoluble fibre, whereas amylose and β-glucan content had no effect. Results show that processing methods can be used to optimise barley foods to reduce postprandial blood glucose responses and factors that may influence satiety.